Physicochemical characterization of natural-like branched-chain glycosides toward formation of hexosomes and vesicles - Ahmad, N.; Ramsch, R.; Esquena, J.; Solans, C.; Tajuddin, Hairul Anuar; Hashim, R. (2012)
Synthetic branched-chain glycolipids have become of great interest in biomimicking research, since they provide a suitable alternative for natural glycolipids, which are difficult to extract from natural resources. Therefore, branched-chain glycolipids obtained by direct syntheses are of utmost interest. In this work, two new branched-chain glycolipids are presented, namely, 2-hexyldecyl beta(alpha)-D-glucoside (2-HDG) and 2-hexyldecyl beta(alpha)-D-maltoside (2-HDM) based on glucose and maltose, respectively. The self-assembly properties of these glycolipids have been studied, observing the phase behavior under thermotropic and lyotropic conditions. Due to their amphiphilic characteristics, 2-HDG and 2-HDM possess rich phase behavior in dry form and in aqueous dispersions. In the thermotropic study, 2-HDG formed a columnar hexagonal liquid crystalline phase, whereas in a binary aqueous system, 2-HDG formed an inverted hexagonal liquid crystalline phase in equilibrium with excess aqueous solution. Furthermore, aqueous dispersions of the hexagonal liquid crystal could be obtained, dispersions known as hexosomes. On the other hand, 2-HDM formed a lamellar liquid crystalline phase (smectic A) in thermotropic conditions, whereas multilamellar vesicles have been observed in equilibrium with aqueous media. Surprisingly, 2-HDM mixed with sodium dodecyl sulfate or aerosol OT induced the formation of more stable unilamellar vesicles. Thus, the branched-chain glycolipids 2-HDG and 2-HDM not only provided alternative nonionic surfactants with rich phase behavior and versatile nanostructures, but also could be used as new drug carrier systems in the future.